The Validity of Online Agreements and The Power of Digital Evidence in Treaty Law in Indonesia - Mochamad Fachrurozi; Harmono Harmono (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
The shift from conventional transactional paradigms to the digital realm creates juridical ambiguity regarding the requirements for the validity of contracts and the admissibility of evidence in civil disputes. This normative legal research aims to analyze the synchronization of Article 1320 of the Civil Code with the ITE Law, as well as evaluate the evidentiary weight of electronic evidence from the perspective of civil procedure law in Indonesia. Using statutory and conceptual approaches, the study finds that electronic contracts remain subject to the classical doctrine of the Civil Code, where the absence of an age verification system on digital platforms has the potential to render agreements voidable. Furthermore, the unilateral imposition of standard clauses frequently undermines the principle of freedom of contract and prejudices the position of consumers. In terms of evidence, the legitimacy of digital evidence continues to be constrained by the absence of adequate forensic operational procedure standards, giving rise to disparities in judicial decisions. The study concludes that the renewal of legal norms has not been accompanied by corresponding technical readiness within the judiciary. It is therefore recommended that a real-time population data system be integrated for the verification of legal subjects, and that a Supreme Court Regulation be issued specifically governing the guidelines for the examination of electronic evidence, in order to ensure legal certainty and consumer protection in cyberspace.